2014
DOI: 10.1093/geront/gnu052
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Leisure Activities and Dimensions of Depressive Symptoms in Later Life: A 12-Year Follow-Up

Abstract: Engagement in a varied range of activities benefits mental health among elders more than participation in any single type of activity among elders. Reducing physical activities can lower positive affect, while the adverse effect may be balanced by increasing social activities. Also, the impact of decreasing intellectual activities on the interpersonal difficulties domain of depressive symptoms may be offset by increasing social activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 52 publications
3
31
0
7
Order By: Relevance
“…Participating in new activities later in life can be particularly satisfying and meaningful, potentially leading to favorable late-life outcomes [47]. A 12-year follow-up study in Taiwan also indicated that, among elderly adults, engagement in a variety of activities was more beneficial than participation in any single type of activity [48]. Thus, the inverse association between intellectual activities and prefrailty/frailty only in women may have been due to new activities they performed.…”
Section: Discussionmentioning
confidence: 99%
“…Participating in new activities later in life can be particularly satisfying and meaningful, potentially leading to favorable late-life outcomes [47]. A 12-year follow-up study in Taiwan also indicated that, among elderly adults, engagement in a variety of activities was more beneficial than participation in any single type of activity [48]. Thus, the inverse association between intellectual activities and prefrailty/frailty only in women may have been due to new activities they performed.…”
Section: Discussionmentioning
confidence: 99%
“…This was a surprise to our research team. Many studies have suggested a strong association between depression and older adults’ development of functional disabilities [ 8 , 46 , 47 ], including that LTA may decrease older adults’ depressive symptoms [ 4 , 48 50 ]. Our findings, however, suggest that LTA participation does not buffer this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Encouraging older adults to explore their interests and participate in LTA or, if already engaging in LTA, to increase their LTA participation, may be an important strategy for maintaining health in future aging societies. Past research studies have encouraged older adults to participate in more varied types of LTA for better mental health and quality of life [ 50 ]. Our study’s findings add that engagement in a wider variety of LTA is crucial for older adults' GFD development, and especially for those with specific sociodemographic characteristics, to experience a slower progression in functional disability and lead to successful aging.…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent findings across studies may arise from differences in social engagement measures [8][9][10][11][12][13][14][15][16]. Combining multiple social activities into one measure makes it difficult to determine whether certain types of social engagement are more relevant to depression [17,18]. The association between social engagement and mental health also differs depending on forms of social engagement, and studies come to different conclusions on this front [19,20].…”
Section: Introductionmentioning
confidence: 99%